Oral health related quality of life in cleft lip and palate patients rehabilitated with conventional prostheses or dental implants - Papi, Piero (J Int Soc Prev Community Dent, 2015)
OBJECTIVES: Cleft lip and/or palate (CLP) is the most common congenital craniofacial abnormality, with a prevalence of 9.92 per 10,000 live births. In treating patients with CLP, oral rehabilitation is definitely a very important phase of the treatment in order to improve the patient's oral health related quality of life (OH-QoL). The aim of this retrospective study is to assess the OH-QoL in patients rehabilitated with different prosthetic options, thus comparing the conventional treatments, which include removable partial dentures and fixed partial dentures, with the implant-supported prostheses. MATERIALS AND METHODS: Sixty-three patients were enrolled in this retrospective survey [44 females (69.84%) and 19 males (30.16%)] with a mean age of 34.93 ± 7.04 years (age range 21–53 years). They were all treated for CLP and rehabilitated with a conventional prosthesis or an implant-supported denture. Two different questionnaires were used in the present study to evaluate patients’ OH-QoL: The Italian version of the 49-item Oral Health Impact Profile (OHIP-49) and the Italian version of the Cleft Evaluation Profile (CEP). Statistical analysis was performed using analysis of variance (ANOVA) test, with a significant P < 0,05. RESULTS: Data analysis revealed that patients rehabilitated with implant-supported dentures and fixed partial dentures showed a good level of satisfaction with their prostheses, scoring low values in the OHIP-49 and high values in the CEP, while subjects with removable partial dentures scored the highest values in the OHIP-49 and the lowest values in the CEP, which means an unsatisfactory feeling (P < 0.05). CONCLUSIONS: OH-QoL is a challenging demand for all prosthodontists. Our results show, clearly, that patients rehabilitated with implant-supported dentures are more satisfied compared to subjects with fixed partial dentures and removable partial dentures.